Synthesis of Ethylenediamine Modified Chitosan Beads for Biodiesel Production Catalyst: A Preliminary Study - Indah Permata Cantika; Muhammad Ali Zulfikar; Handajaya Rusli (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2023)
Biodiesel is an alternative fuel that can be easily produced through transesterification with the assistance of a catalyst. Palm oil is a widely utilized feedstock for biodiesel production due to its abundant availability. In this study, a catalyst was synthesized using chitosan (CS) modified with ethylenediamine (EDA) and cross-linked with epichlorohydrin (ECH) for a catalyst heterogeneous in transesterification reaction. The resulting product (CS/EDA/ECH) was characterized using Fourier-transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). Its performance was evaluated for biodiesel production. The CS/ECH/EDA catalyst achieved optimal reaction conditions with 5% EDA concentration at room temperature, an oil: methanol ratio of 1:1 (v/v), a total volume of 10 mL of oil and methanol, and a catalyst mass of 0.75 grams. The methyl esters formed corresponded to the fatty acid content in palm kernel, namely methyl palmitate, methyl 9,10-octadecadienoate, methyl oleate, methyl 12,13-tetradecadienoate, and methyl stearate with the highest methyl ester conversion is methyl oleate. The CS/ECH/EDA catalyst exhibited consistent performance after three use cycles.